2022
DOI: 10.3389/fonc.2022.960808
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial angiopoietin-2 overexpression in explanted livers identifies subjects at higher risk of recurrence of hepatocellular carcinoma after liver transplantation

Abstract: BackgroundThough the precise criteria for accessing LT are consistently being applied, HCC recurrence (HCC-R_LT) still affects more than 15% of the patients. We analyzed the clinical, histopathological, and biological features of patients with HCC to identify the predictive factors associated with cancer recurrence and survival after LT.MethodsWe retrospectively analyzed 441 patients with HCC who underwent LT in our center. Overall, 70 (15.8%) of them developed HCC-R_LT. We matched them by age at transplant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…It was firstly validated in a prospective multicenter cohort of patients with HCC treated with sorafenib conducted in Italy, then another in Japan, and also in patients treated with regorafenib, ramucirumab, and radioembolization. [56][57][58][59][60] Additionally, a recent meta-analysis evaluating sorafenib benefit in patients with intermediate/advanced HCC, showed that macro-vascular invasion and extrahepatic spread were significantly associated with rapid progression at multivariable meta-regression analysis. [58] This may seem self-evident since these variables related to tumor burden are those which define the advanced stage according to BCLC classification compared to the intermediate stage.…”
Section: The Pattern Of Progression As a Tool For Identifying Indolen...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was firstly validated in a prospective multicenter cohort of patients with HCC treated with sorafenib conducted in Italy, then another in Japan, and also in patients treated with regorafenib, ramucirumab, and radioembolization. [56][57][58][59][60] Additionally, a recent meta-analysis evaluating sorafenib benefit in patients with intermediate/advanced HCC, showed that macro-vascular invasion and extrahepatic spread were significantly associated with rapid progression at multivariable meta-regression analysis. [58] This may seem self-evident since these variables related to tumor burden are those which define the advanced stage according to BCLC classification compared to the intermediate stage.…”
Section: The Pattern Of Progression As a Tool For Identifying Indolen...mentioning
confidence: 99%
“…In fact, presence or absence of many biological features, that are classically linked to aggressiveness of HCC (microvascular invasion, satellite nodules, diffuse infiltrating growth, poorly differentiated HCC, mixed HCC-cholangiocarcinoma, "poor prognostic molecular signature", and high AFP), are associated with high risk of recurrence after resection or LT, failure of local control with local regional therapies, early progression, and finally lead to poor prognosis. In this line, an Italian study showed that endothelial angiopoietin-2 overexpression in explanted livers independently predicts the risk of HCC recurrence and death after LT. [60] However, except for AFP in the field of LT, which is used as a surrogate to differentiate tumor aggressiveness, there is no consensus on how to incorporate huge molecular heterogeneity into tumor staging.…”
Section: The Pattern Of Progression As a Tool For Identifying Indolen...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that these patients, who were only eligible for systemic therapy after failing more curative treatments, were at an advanced stage with expected extra-hepatic spread, which aligns with high podoplanin levels. From this perspective, the elevated endothelial Ang2 levels also indicate aggressive disease [25,26]. Notably, females, showing the highest podoplanin and Ang2 levels, responded better to TKI therapy, had longer overall survival, and remained on treatment longer compared to males, who exhibited lower levels of these markers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experiencing HCC recurrence showed significantly increased expression of angiopoietin-2 in tumor endothelium but not in the hepatocyte at explant pathology. Univariate analysis identified BMI, log AFP at transplant, endothelial angiopoietin-2 expression, Milan criteria, Metroticket AFP score, and the AFP model as significantly associated with recurrence, while in multivariate analysis angiopoietin-2 expression was the only independent factor associated with recurrence (HR: 5.634, 95% CI 2.597-12.294, p < 0.001) [50].…”
Section: Post-lt Hcc Recurrencementioning
confidence: 93%